Biventricular pacemaker and defibrillator implantation in patients with chronic heart failure in China. (9th November 2020) - Huang, Dejia; Hua, Wei; Fang, Quan; Yan, Ji; Su, Yangang; Liu, Bing; Xu, Yuanning; Peng, Yong
Abstract: Aims: This study aims to investigate the current status of biventricular pacemaker and defibrillator implantation in chronic heart failure (CHF) patients with indications for primary prevention of sudden cardiac death (SCD) in China and the effects of cardiac resynchronization therapy (CRT)‐pacemaker (P) and CRT‐defibrillator (D) implantation on the clinical prognosis of CHF among patients undergoing CRT. Methods and results: Overall, 798 consecutive patients who had devices implanted (implantable cardioverter defibrillator: 199, CRT‐D: 362, and CRT‐P: 237) from May 2012 to July 2013 in POSCD‐China, a multicentric prospective cohort study, were enrolled. The primary endpoint was all‐cause death, and the secondary endpoint was SCD. In total, 71.3% of patients had non‐ischaemic CHF. The mean follow‐up time was 27.7 ± 12.0 months, and death occurred in 158 cases, with 35 cases of SCD. CHF was the main cause of death (68.4%), followed by sudden death (22.2%). In the CRT‐P group, the SCD rate was 8.0%, which was much higher than that in the CRT‐D (3.3%) and implantable cardioverter defibrillator (2.0%) groups. No significant differences were identified in the all‐cause death rate between the CRT‐D and CRT‐P groups (CRT‐D vs. CRT‐P, 20.4% vs. 19.4%, P  = 0.840). Conclusions: In China, among CHF patients with indications for primary prevention of SCD who received device implantation, non‐ischaemic CHF was the main aetiology, and the most important cause of death was heart failure. No differences in all‐cause death were observed between the CRT‐D and CRT‐P groups, but the CRT‐D group had a lower SCD rate than the CRT‐P group.